Characterization and virulence of two indigenous entomopathogenic fungal isolates from decayed oil palm empty fruit bunches against Spodoptera litura (Lepidoptera: Noctuidae) - ABDUL SAHID; PINTAKA KUSUMANINGTYAS (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Kusumaningtyas P. 2023. Characterization and virulence of two indigenous entomopathogenic fungal isolates from decayed oil palm empty fruit bunches against Spodoptera litura (Lepidoptera: Noctuidae). Biodiversitas 24: 1192-1199. The objective of this study was to characterize (morpho-molecular characterization and lignocellulolytic activity) and evaluate the virulence of two indigenous EPF isolates from decayed oil palm empty fruit bunched (OPEFB) against the common cutworm Spodoptera litura Fabr. (Lepidoptera: Noctuidae) under laboratory conditions. The fungi were isolated from OPEFB samples collected from oil palm plantations in Indonesia, and were identified as Fusarium keratoplasticum (isolate TKKS-1) and Metarhizium anisopliae (isolate TKKS-2). Both fungal isolates were tested for their pathogenicity against the 3rd instar larvae of Spodoptera litura Fabr. at the concentration of 1 × 106 conidia/mL. Both fungal isolates showed 100% mortality rate after 7 days of application. Virulence of the EPF isolates against the 3rd instar of S. litura larvae was estimated based on the LC50 values calculated using probit regression analysis. The LC50 values of M. anisopliae and F. keratoplasticum isolates were 1.41 × 105 and 1.02 × 106 conidia/mL, respectively. The LT50 at the concentration of 1 × 106 conidia/mL was 3.82 days for F. keratoplasticum and 3.52 days for M. anisopliae. M. anisopliae showed cellulolytic activity, while F. keratoplasticum exhibited ligninolytic activity. This finding suggests that two EPFs isolated from OPEFBs were highly virulent against S. litura larvae and potential decomposers for lignocellulose. These characteristics indicated significant biocontrol and decomposing properties of lignocellulose waste.